Beyond widowhood: Do prior discovered themes that describe the experiences of older Australian widowed women persist over time?. Issue 7 (2nd October 2016) - Kennaugh, Robyn; Byles, Julie; Tavener, Meredith
ABSTRACT: In previous cross-sectional studies researchers have explored the experiences of widowed women in the 1921–1926 cohort of the Australian Longitudinal Study on Women's Health and identified three major themes: health, social relationships and support, and financial and structural issues. In the current study the authors examine longitudinal data collected over 15 years to assess whether these themes persisted and/or evolved over time. The sample included 162 widowed women aged 70–90 years. Thematic analysis was used with a constant comparison method. Many women reported good health despite managing comorbidities. Social relationships frequently shifted from friends to family to more formal support. Most financial and structural issues related to managing increasing health costs as women aged. These results confirmed that the three major themes previously reported persisted over time, and underscore the importance of continuing to support women, and their changing needs, well beyond the initial period of bereavement.